2012
DOI: 10.1097/rhu.0b013e3182676b6b
|View full text |Cite
|
Sign up to set email alerts
|

Spanning Generations—Appointment Reminder Preferences Among Patients With Rheumatic Diseases

Abstract: Improved rheumatology clinic attendance would be beneficial given the need for disease assessment and medication monitoring. Most patients view appointment reminders favorably; however, no studies have assessed the modality and timing preferences of patients in a US rheumatology clinic. Modality, but not timing, preferences vary with generational age. The preference for newer modalities such as text/SMS reminder was predominately observed in the patients of generation Y, a population prone to clinic nonattenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Previous studies show inconsistent results in terms of how age affects electronic system usage. Studies have found that older patients are less likely to use the Internet7 and phone texting,20 and that middle aged patients are more likely to use electronic messaging16 and are more likely to activate electronic patient portal accounts 6. In contrast, this study found that older adults tended to send more messages, and that the Baby Boom generation was more likely to send zero messages.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Previous studies show inconsistent results in terms of how age affects electronic system usage. Studies have found that older patients are less likely to use the Internet7 and phone texting,20 and that middle aged patients are more likely to use electronic messaging16 and are more likely to activate electronic patient portal accounts 6. In contrast, this study found that older adults tended to send more messages, and that the Baby Boom generation was more likely to send zero messages.…”
Section: Discussioncontrasting
confidence: 70%
“…From the EHR we extracted age, gender, race and ethnicity, language preference, insurance status, number of office visits during the year, ZIP code and clinical diagnoses for the following chronic conditions: diabetes, hypertension, hyperlipidaemia, depression, congestive heart failure, asthma, drug abuse, alcoholism and HIV. Age was split into categories based on generation, which has previously been used to characterise Internet usage 9,19,20. People were categorised into the G.I.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with studies finding varied preferences for receiving automatic reminders [ 14 , 15 , 34 - 37 ]. Younger age has been associated with an increased preference for text messages over phone calls or emails [ 15 , 36 ]; however, individuals’ familiarity with sending or receiving text messages is a greater predictor of patient acceptance [ 15 , 37 ]. Given that adult use of text messaging has increased dramatically over the last decade [ 38 , 39 ], more and more people will likely choose texting as their preferred communication modality in the future.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Strategies using appointment reminders have been generally well received by patients. 3 , 14 16 Traditionally, HCOs have adopted a one-size-fits-all approach to appointment reminders, where one type of reminder is sent to all patients. 17 However, research suggests that peoples’ preferences and attitudes impact their behavior.…”
Section: Introductionmentioning
confidence: 99%